Баймер: роман / Юрий Никитин - Никитин Юрий Александрович (Цикл "Грядущие романы", 2004)
Экземпляры: аб. (2012) / Инвентарный номер: 49305 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 62 / ББК: 84(2Рос=Рус)6